Letter from Max Bredig to H. Jermain Creighton, June 6, 1939 - Bredig, Max Albert (1939)
Max Bredig (1902-1977) writes to H. Jermain Creighton, a professor of Chemistry at Swarthmore College, with updates on his family. His father, Georg Bredig (1868-1944), has been given permission to leave Germany for Holland, though Max feels pressure to have him immigrate to the United States. Max's sister and brother-in-law, Marianne (1903-1986) and Viktor Homburger (1888-1968), have received a permit to stay in England until they are able to immigrate to the United States.
Keywords: Bredig, Max Albert, 1902-1977; Creighton, H. Jermain; Emigration and immigration; Bredig, Georg, 1868-1944